2020
DOI: 10.1117/1.jbo.25.5.056005
|View full text |Cite
|
Sign up to set email alerts
|

Laser speckle contrast imaging system using nanosecond pulse laser source

Abstract: Significance: Nanosecond-pulsed laser has proven to be used to obtain the velocity of blood using the speckle contrast method. Without the scanning time, it has potential for achieving fast two-dimensional blood flow images in a photoacoustic imaging system with the same pulsed laser.Aim: Our study aimed to evaluate the qualities of regional cerebral blood flow (rCBF) obtained in a laser speckle contrast imaging (LSCI) system using continuous wave (cw) and nanosecond pulse laser sources.Approach: First, a LSCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Then, a stack of 30 raw images was stored and processed. Equation ( 2) was used to calculate speckle contrast (K) [26].…”
Section: The Rcbf Images Obtained By Lscimentioning
confidence: 99%
“…Then, a stack of 30 raw images was stored and processed. Equation ( 2) was used to calculate speckle contrast (K) [26].…”
Section: The Rcbf Images Obtained By Lscimentioning
confidence: 99%
“…A series of works [180][181][182] presents studies of CBF and brain electrophysiology monitoring before, during, and after asphyxial cardiac arrest and further resuscitation using LSCI and LSCI combined with electroencephalography. Zhao et al [183] showed the possibility to use nanosecond pulse laser sources in LSCI setups for CBF measurements. The use of pulsed light sources will possibly allow for combined LSCIphotoacoustic imaging.…”
Section: Brain Vasculature Assessmentmentioning
confidence: 99%
“…The exposure time of the CCD was set as 20 ms, and the images were acquired through the programming software at 20 Hz. The following equation ( 2) was used to calculate speckle contrast ( K ) [5] .…”
Section: Brain Blood Flow Observation Using Laser Speckle Contrast Im...mentioning
confidence: 99%